Photovolitaics Concept Integrated on the Grid With the STT-PLN Building - Anggara Trisna Nugraha; Dimas Bayu Dwi Saputra; Rama Arya Sobhita; Muhammad Bilhaq Ashlah (P3M Politeknik Perkapalan Negeri Surabaya, 2024)
As we enter the 21st century, concerns over dwindling oil and gas reserves have become more pronounced. With energy demand on the rise, particularly in developed nations, projections indicate a 70% increase between 2000 and 2030. By the year 2017, global electricity demand is expected to reach 25.4 trillion kWh. Solar energy emerges as a promising solution, especially in regions like Indonesia, where the entire mainland covers roughly 2 million km2 and receives an average daily radiation distribution of 4.8 kWh/m2. This translates to a solar energy potential of 5.10 mW, equivalent to 112,000 GWp. Technically speaking, solar panels have shown an efficiency improvement of 17.4%. When considering components and the quality absorbed by solar power plants (PLTS) synchronized by KWH EXIM, calculations reveal a performance ratio of 81%, confirming the technical feasibility of implementing such systems